GAME PERAKITAN KOMPUTER BERBASIS MOBILE MENGGUNAKAN METODE FINITE STATE MACHINES (FSM) - Susanti , M.IT; Aifan Aifan (Universitas Islam Kuantan Singingi, 2019)
Games are entertainment media in the form of multimedia that is made as attractive as possible that is played using electronic media to provide satisfaction to its users. Aside from being a means of entertainment, games can also be used as a means of learning to increase knowledge. But the development of games that contain elements of education is very difficult to find. Various alternative and programming innovations were carried out to make educational media to facilitate the learning process, including Computer Assembling Games. Computer assembly is to assemble all computer components to become a PC that is ready to use. However, the assembly process is difficult because it requires adequate equipment and space. For that you need a media that can facilitate the process of learning to assemble a computer. This game is made based on Android so it makes it easier for users to play it. The method used in making this game is Finite State Machines (FSM). With the existence of this game is expected to increase knowledge and facilitate the learning process of assembling computers.